If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8n + -3)(5n + 6) = 0 Reorder the terms: (-3 + 8n)(5n + 6) = 0 Reorder the terms: (-3 + 8n)(6 + 5n) = 0 Multiply (-3 + 8n) * (6 + 5n) (-3(6 + 5n) + 8n * (6 + 5n)) = 0 ((6 * -3 + 5n * -3) + 8n * (6 + 5n)) = 0 ((-18 + -15n) + 8n * (6 + 5n)) = 0 (-18 + -15n + (6 * 8n + 5n * 8n)) = 0 (-18 + -15n + (48n + 40n2)) = 0 Combine like terms: -15n + 48n = 33n (-18 + 33n + 40n2) = 0 Solving -18 + 33n + 40n2 = 0 Solving for variable 'n'. Factor a trinomial. (-6 + -5n)(3 + -8n) = 0Subproblem 1
Set the factor '(-6 + -5n)' equal to zero and attempt to solve: Simplifying -6 + -5n = 0 Solving -6 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -5n = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -5n = 0 + 6 -5n = 0 + 6 Combine like terms: 0 + 6 = 6 -5n = 6 Divide each side by '-5'. n = -1.2 Simplifying n = -1.2Subproblem 2
Set the factor '(3 + -8n)' equal to zero and attempt to solve: Simplifying 3 + -8n = 0 Solving 3 + -8n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -8n = 0 + -3 -8n = 0 + -3 Combine like terms: 0 + -3 = -3 -8n = -3 Divide each side by '-8'. n = 0.375 Simplifying n = 0.375Solution
n = {-1.2, 0.375}
| -5(10r+2)+3(6r+8)= | | 7h^3-35h^2-42h= | | (b+3)(b-1)=0 | | 20x^3=0 | | x^2+0x=16 | | 5y=3y+10 | | x^2-5x-115=11 | | 5x-4x+10=48 | | 4x-5=8x | | 3-1*x=2x-4 | | 4+17y-1=9y+107-7y | | 4-5(3x-2)+6x=7-(5x+1)+3-5x | | 3y^2+42y+147=0 | | 3(6x-5)-2(4x-12)=9x+12 | | 0*x=x^2-4x | | 7s+19s=52 | | 8/x+3=0 | | 0*x=2x-4 | | W^2=-42-13w | | -3x=x^2-4x | | 5/2y+4y/(y-9)=-9/2 | | -5x=2x-4 | | (-5x)=2x-4 | | -4(2b+1)+(9b-5)=0 | | 19j+16=8 | | (-5)*(x)=2x-4 | | 5r^2+34r+45=0 | | 5.9q-3.8-5.5q=-0.6q-5.4 | | 2*x=x^2-4*x | | 7.3x-2x=-4x+4 | | 2(x)=x*x-4x | | 3x-5+2x+8=x+4+3x-12 |